ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGEMBANGAN KARIR KARYAWAN PADA PT. BANK NEGARA INDONEESIA (PERSERO) TBK CABANG PEKANBARU - Depri Egota; Endang Sutrisna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Career development is very important for a company, career development is also very helpful employees in analyzing their willingness and interest to achieve individual career employees in accordance with the needs and development of the company. purpose of this study was to determine and analyze the factors that influence the career development of employees at PT. Bank Negara Indonesia (Persero) Tbk Branch PekanbaruThe method used in this research is descriptive and analytical techniques used are qualitative analysis. The sampling technique used was simple random sampling with a population of 56 people and the amount of sample is 50 respondents. Data were obtained through interviews and questionnaires that measured using a Likert scale.The results of this study indicate that the factors that influence the career development of employees at PT. Bank Negara Indonesia (Persero) Tbk Branch Pekanbaru indicate the criteria agreed or appropriate.keywords : Analysis, factors Career Development, PT. Bank Negara Indonesia (Persero) Tbk Branch Pekanbaru